PENGARUH ATRIBUT PRODUK, WORD OF MOUTH, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN” (STUDI KASUS PEMBELIAN RE:ON COMICS PADA ANGGOTA REONITES) - Annisa Nur Rahma Muliati; Sri Suryoko (Jurnal Ilmu Administrasi Bisnis, 2018)
This research is motivated by the development of local comics, one of them isRe:ON Comics. The presence of Re:ON Comics has recieved public support sothat Reonites group was formed and expected to increase its sales. Thedevelopment of Re:ON Comics experienced problems with the emergence ofconsumer complaints in purchasing, which caused the spread of the productcouldn’t be simultaneously happened in Indonesia and reduce the percentage ofsales increase in 2013 to 2015.Purchase decision can be affected by a variety of factors, both internal andexternal factors. The purpose of this research is to know the influence of productattribute, word of mouth and life style on purchase decision (a case study of Re:ONComics purchasing on reonites members).The method in this study used quantitative research method and explanatoryresearch type that test hypotheses between variables with other variables thatinfluence each other. This study used purposive sampling technique againstReonites members on Facebook for 100 respondents. Data collecting using aquestionnaire and interview. Data analysis using simple and multiple linierregression analysis in IBM SPSS.Results of statistical analysis known that together product attribute, word of mouthand life style against purchase decision based on the coefficient of determination38,3%, value F count (19,865)>F table (2,70) with significance of 0,000<level ofsignificance 0,05 then it can be seen that “ There is influence of product attribute,word of mouth and life style to purchase decision.The conclusion from this study is that there is a positive and significant influencebetween product attribute, word of mouth and life style to purchase decision (acase study of Re:ON Comics purchasing on reonites members). Research suggestthat Publisher of Re:ON Comics improve quality of product attribute along withmore understand about word of mouth and the lifestyle on Reonites to increase thepurchase decision by consumers.